The Meaning of Symbols in the Lyrics of Balinese Songs by Dek Ulik: A Semiotic Study by Roland Barthes - Ni Komang Mahatma Devi S. Yadnyaseni; Ellyana Hinta; Nuramila (Raja Zulkarnain Education Foundation, 2026)
Contemporary Balinese music, particularly the works of Dek Ulik, has experienced rapid development in the digital era, but the younger generation’s appreciation of the depth of symbolic meaning contained within it is still very limited. This study aims to describe the symbolic signs in the lyrics of Balinese songs by Dek Ulik that reflect the culture and society of Balinese society, analyze the meaning of each symbol found, and describe its relevance to learning Indonesian. This study uses a descriptive qualitative approach with Roland Barthes’s semiotic analysis method that dissects meaning through three levels, namely denotation, connotation, and myth. The object of the study is the lyrics of five Balinese songs by Dek Ulik, namely Ratih Kamajaya, Sanjiwani, Tresna Kanti Pawah, Suksma Hyang Widhi, and Nyerahang Dewek. The results show that the lyrics of these songs contain various signs that through the process of cultural convention develop into symbols. Each symbol has layers of meaning, ranging from literal meaning to ideological meaning that reflects the life views of Balinese Hindu society. Furthermore, these symbols have substantive relevance to Indonesian language learning in the Independent Curriculum in Phases D, E, and F. This study concludes that the lyrics of the song Dek Ulik are not merely a product of entertainment art, but rather a semiotic construction rich in cultural, philosophical, and ideological content of the Balinese people. This finding also confirms that regional artworks have great potential as contextual and authentic teaching materials in Indonesian language learning.